1 | initial version |

The solutions are correct but they are not fully simplified.

```
sage: f= x^2 - (1 + I)*x + 6 + 3*I
sage: solve(f==0,x)
[x == -1/2*sqrt(-10*I - 24) + 1/2*I + 1/2, x == 1/2*sqrt(-10*I - 24) + 1/2*I + 1/2]
```

For each solution, you can simplify its right-hand-side as follows:

```
sage: [s.rhs().full_simplify() for s in solve(f==0,x)]
[3*I, -2*I + 1]
```

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.